EDUCATIONAL RESEARCH: : A GENERAL REVIEW FROM ITS FOUNDATIONS - Díaz Pérez, Alfredo; Rodríguez, Jesús; Rojo, Gonzalo; Maldonado, Alexis; Scandela, Stephanie (Revista Arbitrada Formación Gerencial, 2024)
The purpose of this essay is to expose the most outstanding aspects of educational research, based on a critical-reflexive perspective on teaching praxis and the elements that are directly or indirectly linked to the investigative process. The contributions of Azuaje and González (2018), Babu (2019), Colina (2019), Marqués, (2010), Martínez, Aponte & Urdaneta (2007), Morin (1995), Piña (2013), Ruedas, Ríos y Nieves (2009), among others. Own criteria are exposed, based on the authorial positions that allowed elucidating how educational research manifests itself in reality, since reflections are generated that must be considered by teachers, students and other actors in the educational process, by virtue of implementing changes. substantial in educational praxis and the interrelationships between its elements, components, factors and interest groups. Finally, reflections are generated aimed at creating awareness about the need to carry out research in the educational field in order to generate assertive solutions to the real problems of the context.